Attitudes of mental health professionals towards persons with schizophrenia: a transcultural comparison between Switzerland and Brazil (Archives of Clinical Psychiatry, 2012)
BACKGROUND: Stigmatization is an important issue in the treatment and course of schizophrenia. The maintenance of stigmatizing attitudes may be related to socio-cultural factors. OBJECTIVES: To compare stigmatizing attitudes of mental health professionals in the culturally diverse countries Brazil and Switzerland. METHODS: We analyzed data of two broad stigmatization surveys from Switzerland and Brazil by focusing on the social distance and attitudes of mental health professionals towards the acceptance of side effects of psychopharmacological treatment. RESULTS: Swiss mental health professionals showed significantly higher levels of social distance than their Brazilian counterparts. There was also a weak effect of age as well as an interaction effect between origin and age. With respect to the acceptance of side effects, the effect of origin was rather weak. With the exception of drug dependence, Swiss professionals' acceptance of long-lasting side effects was significantly higher than for their counterparts in Brazil. DISCUSSION: The strong association between origin and social distance may be related to the socio-cultural background of the mental health professionals. In comparison with Switzerland, Brazil is very heterogeneous in terms of ethnicity and socio-economic structure. The distinct acceptance of side effects may additionally be related to the more sophisticated medicaments (i.e. new generation of antipsychotic drugs) commonly used in Switzerland.